2020
DOI: 10.1088/2053-1591/ab6a48
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical characterization and experimental modal analysis of 3D Printed ABS, PC and PC-ABS materials

Abstract: Additive manufacturing (AM) process builds the parts, layer by layer precisely from Computer-Aided Design (CAD) models, whereas traditional subtractive manufacturing process removes layers from materials to attain the desired shape. Of late Rapid prototyped (RP) parts are used for the direct production of components for manufacturing and testing in the industries. Understanding material, machine used along with the process variables that affect the strength of the final part gains importance as the parts can b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
33
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 62 publications
(34 citation statements)
references
References 21 publications
1
33
0
Order By: Relevance
“…For instance, the low tensile strength measurement of 15 MPa for ABS was due to testing in the transverse loading direction compared to the higher measurements of tensile strength closer to 30 MPa based on the build layer orientation. Similar differences were observed for polycarbonate materials based on their processing and chemicals used to manufacture the material [ 35 , 36 ]. One study concluded that a blend of polycarbonate referred to as a bio-based polycarbonate had a slightly higher strength of 65 MPa and significantly higher elastic modulus of 2100 MPa than a polycarbonate manufactured using fossil fuels with 62 MPa strength and 1500 MPa elastic modulus [ 35 ].…”
Section: Materials Capabilitiessupporting
confidence: 60%
See 1 more Smart Citation
“…For instance, the low tensile strength measurement of 15 MPa for ABS was due to testing in the transverse loading direction compared to the higher measurements of tensile strength closer to 30 MPa based on the build layer orientation. Similar differences were observed for polycarbonate materials based on their processing and chemicals used to manufacture the material [ 35 , 36 ]. One study concluded that a blend of polycarbonate referred to as a bio-based polycarbonate had a slightly higher strength of 65 MPa and significantly higher elastic modulus of 2100 MPa than a polycarbonate manufactured using fossil fuels with 62 MPa strength and 1500 MPa elastic modulus [ 35 ].…”
Section: Materials Capabilitiessupporting
confidence: 60%
“…In Table 1 , multiple studies are reported for comparisons of ABS materials that all demonstrated similar, but slightly different mechanical properties [ 34 , 35 , 36 ], such as tensile strength ranging from 15 MPa to 38 MPa. These differences are accounted for in part because of the different processing temperatures and printing parameters used to construct parts, the slightly different proportions of monomers in ABS’s structure, and the tested part’s orientation.…”
Section: Materials Capabilitiesmentioning
confidence: 99%
“…Unfortunately, the polymer components still do not show the expected properties; therefore, high functionality of the material can be achieved by strengthening the polymer matrix. Many scientists have attempted to combine the properties of PC with such a well-known material as acrylonitrile-butadiene-styrene copolymer [ 14 , 15 , 16 , 17 , 18 ] and poly(ethylene terephthalate) [ 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…Telematics have an impact on three major areas: social (a decreasing number of accidents), economic (a fixed and operating costs reduction) and environmental (a demand for energy or lowering pollution emissions, mainly CO 2 and NOx) [16] (pp. [50][51][52][53][54][55]. Without such systems, the efficiency and functioning of urban freight transport would stay at low level.…”
Section: Telematics In Road Transportmentioning
confidence: 99%
“…Beside standard filaments, references indicate composites as printing material [35,43,47]. The market also offers other filaments with special properties: see [43,51,52].…”
Section: Polymers and Thermoplastic Elastomersmentioning
confidence: 99%